Parents’ Supports Toward EFL Students’ Excellent Class English Communicative Competence in Sma Antartika Sidoarjo - Hidayatullah, Anggiek Safaat; Wafiroh, Laili Hibatin; Andanty, Ferra Dian (Universitas PGRI Adi Buana Surabaya, 2024)
The purpose of this study is to explore the types and implementation of parental support for EFL students' advanced classes that focus on communicative competence. This study is formulated based on research questions. Therefore, the problem identified is that English is an important language and students feel that oral and written subjects in English learning are problematic. This study uses qualitative case studies to answer the research questions. Semi-structured interviews were used to collect data. Six parents and their children participated in the interviews. The data collection will be validated using theoretical triangulation. The findings represent the implementation of parental support. It can be concluded that there are three types of support and implementation. Parents need to improve their knowledge of English, because English has become very important, even for everyday use.